(untitled) (Journal of Comparative & International Higher Education, 2024)
In 2012, the Vietnamese government enacted the institutional autonomy policy to support the reform process of the higher education system. The autonomy policy signifies the transfer of decision-making authority from ministries to public universities to increase university performance and competitiveness in the globalized knowledge economy. This paper examines the nature of autonomy as a new form of governance in Vietnamese higher education through the lens of agency theory. I used thematic analysis to analyze policy documents released by the Vietnamese government between 1993 and 2021. The findings indicate autonomy means Vietnamese public universities have authority to make decisions on primary activities; yet they must be accountable for their decision-making and responsible for funding sources. The study contributes to the literature on comparative and international higher education by providing a better understanding of autonomy in a post-Soviet context and informing a transformative approach to policy practices for the higher education reform.